The Fair Wage-Effort Hypothesis and Unemployment - Akerlof, George A.; Yellen, Janet L. (Quarterly Journal of Economics, 1990)
This paper introduces the fair wage-effort hypothesis and explores its implications. This hypothesis is motivated by equity theory in social psychology and social exchange theory in sociology. According to the fair wage-effort hypothesis, workers proportionately withdraw effort as their actual wage falls short of their fair wage. Such behavior causes unemployment and is also consistent with observed cross-section wage differentials and unemployment patterns.